Knowledge of dental and oral health in patients treated by students of Dentistry Professional Program - Pramudita, Dinar Windiayu (Padjadjaran Journal of Dentistry, 2013)
Introduction: Behaviors is to maintain oral health in a person will be begin to improve the person’s knowledge about oral health. Dental health promotion to patients can be done by professional program students. These efforts are made individually, while in the dental chair or commonly known as chairsidetalk. This study was a descriptive study with survey technique. Data was  collected using a questionnaire sheet. The purpose of this study to assess knowledge of oral health in patients who treated by professional dentistry program students RSGM FKG UNPAD. Methods: This study was a descriptive study with survey technique. Sample of this study were patients who were treated by dentistry professional program students RSGM FKG UNPAD, which was purposive random sampling method, and the number of samples obtained were 224 patients. Results: The results shows that patients treated in the dentistry professional program students RSGM FKG UNPAD have a good level of knowledge,  total of 116 respondents (51.79%), the second highest frequency of 82 respondents (36.61%) had a level of knowledge and at least enough of the respondents were 26 respondents (11.61%) had a level of knowledge is lacking. Conclusion: Conclusions the study are patients who had received care from the dentistry professional program students in  RSGM FKG UNPAD has a good level of knowledge about oral health.